Mitochondria: the gatekeepers between metabolism and immunity - Trinchese, Giovanna; Cimmino, Fabiano; Catapano, Angela; Cavaliere, Gina; Mollica, Maria Pina (Frontiers in Immunology, 2024)
Metabolism and immunity are crucial monitors of the whole-body homeostasis. All cells require energy to perform their basic functions. One of the most important metabolic skills of the cell is the ability to optimally adapt metabolism according to demand or availability, known as metabolic flexibility. The immune cells, first line of host defense that circulate in the body and migrate between tissues, need to function also in environments in which nutrients are not always available. The resilience of immune cells consists precisely in their high adaptive capacity, a challenge that arises especially in the framework of sustained immune responses. Pubmed and Scopus databases were consulted to construct the extensive background explored in this review, from the Kennedy and Lehninger studies on mitochondrial biochemistry of the 1950s to the most recent findings on immunometabolism. In detail, we first focus on how metabolic reconfiguration influences the action steps of the immune system and modulates immune cell fate and function. Then, we highlighted the evidence for considering mitochondria, besides conventional cellular energy suppliers, as the powerhouses of immunometabolism. Finally, we explored the main immunometabolic hubs in the organism emphasizing in them the reciprocal impact between metabolic and immune components in both physiological and pathological conditions.